2020
DOI: 10.1103/physrevb.101.075120
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics of palladium in the presence of electronic correlations

Abstract: We compute the phonon dispersion, density of states, and the Grüneisen parameters of bulk palladium in the combined Density Functional Theory and Dynamical Mean-Field Theory. When electronic correlations are taken into account we find a good agreement with the experimentally measured phonon spectra, and ground state properties (equilibrium lattice parameter and bulk modulus) in comparison with density functional theory results. At the same time we demonstrate that the previously predicted softening of the phon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
5
2
Order By: Relevance
“…The wave-vectors at which the Kohn anomaly arise are the nesting vectors of the Fermi surface which for Pd are the tube structures along X − W direction. In contrast to DFT results, for which the phonon frequency remains essentially constant in a large temperature range, correlation effects reduce the restoring force of the ionic displacements at low temperatures, leading to a mode softening 22 .…”
Section: Introductioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The wave-vectors at which the Kohn anomaly arise are the nesting vectors of the Fermi surface which for Pd are the tube structures along X − W direction. In contrast to DFT results, for which the phonon frequency remains essentially constant in a large temperature range, correlation effects reduce the restoring force of the ionic displacements at low temperatures, leading to a mode softening 22 .…”
Section: Introductioncontrasting
confidence: 67%
“…Using the same LDA+DMFT method we computed the changes in the phonon dispersions and phonon density of states of Pd under a hydro-static pressure. We found that electronic correlations at finite temperatures strongly renormalize the phonon frequencies and are the source of the so-called Kohn anomaly 22 . The wave-vectors at which the Kohn anomaly arise are the nesting vectors of the Fermi surface which for Pd are the tube structures along X − W direction.…”
Section: Introductionmentioning
confidence: 95%
“…The study of electron-phonon interactions (EPIs) goes back to the early days of solid-state theory. They are important for our understanding of basic material properties such as effective masses [1][2][3][4] and lattice constants [5,6]. Furthermore, this interaction is responsible for phase transitions, such as conventional superconductivity [7][8][9][10][11][12][13][14][15][16][17][18] and charge-density waves (CDWs) [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The study of electron-phonon interactions (EPIs) goes back to the early days of solid state theory. They are important for our understanding of basic material parameters, like effective masses of electrons [1][2][3][4] and lattice constants [5,6]. Furthermore, this interaction is responsible for phase transitions, such as conventional superconductivity [7][8][9][10][11][12][13][14][15][16][17][18] and charge-density waves [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%